The 44-Day War in Nagorno Karabakh and South Caucasus Geopolitical Role Transformation Processes - Gevondyan, Alen (YSU Journal of International Affairs, 2022)
44-Day War in Nagorno Karabakh dramatically changed the geopolitical role of the South Caucasus Region. If previously there was some kind of delicate balance of power in the region, this War changed it. The new one has not been settled yet. The article analyzes and assesses the chain of factors which make an impact on the geopolitical role of the region and achievement of the regional balance. Particularly, we analyze the regional conflicts, the energetic-communication role of the South Caucasus, the methods of change of power and foreign policy doctrines of the regional states, as well as the changed roles of the Russian Federation and Turkey.